Impact of the capture time on power saturation of quantum-well diode lasers. (21st February 2023) - Boni, A; Wenzel, H; Crump, P
Abstract: Injected electrons and holes are captured into quantum wells with a non-vanishing time. Simulation results are presented, showing that this results in a non-equilibrium of free and bound carriers in a diode laser. Analysis of an exemplary diode laser structure is used to show that if the capture time is too large, the carrier densities in regions adjacent to the quantum well rise strongly beyond their values at threshold at very high output power. This results in an increase of the free carrier absorption and the non-stimulated recombination, causing a reduction of the slope efficiency and a downwards-bending of the power-current characteristics (power saturation), consistent with experimental results. For the layer structure studied, the additional losses due to accumulation of holes in the n-doped region is predicted to be the dominant effect.